Nanotechnologies for the Life Sciences 2003
DOI: 10.1002/9783527610419.ntls0023
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles for Crossing Biological Membranes

Abstract: The sections in this article are Introduction Cell Membranes Functions of Biological Membranes Kinetic and Thermodynamic Aspects of Biological Membranes Problems of Drugs Crossing through Biological Membranes Through the Skin Mechanical Irritation of Skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 121 publications
2
21
0
Order By: Relevance
“…We observed in HE-stained DRG neurons a prominent vacuole formation and under-representation of the largest diameter clear neurons (type A) and possibly an overrepresentation of small, more basophilic neurons in DN animals (type B) compared with controls. After 25 Mg-PMC 16 administration, we observed notable improvement changes in DRG neurons compared with the DN group, but we did not find any observable difference in the 24 Mg PMC16 or MgCl 2 groups in comparison with DN animals ( fig. 1A-E).…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…We observed in HE-stained DRG neurons a prominent vacuole formation and under-representation of the largest diameter clear neurons (type A) and possibly an overrepresentation of small, more basophilic neurons in DN animals (type B) compared with controls. After 25 Mg-PMC 16 administration, we observed notable improvement changes in DRG neurons compared with the DN group, but we did not find any observable difference in the 24 Mg PMC16 or MgCl 2 groups in comparison with DN animals ( fig. 1A-E).…”
Section: Resultsmentioning
confidence: 56%
“…We showed that STZ-induced DN caused morphological abnormalities in DRG neurons comprising changes in area, diameter and number of A and B cells as well as motor dysfunction in DN. Moreover, our findings indicated that administration of 25 Mg-PMC16 as a magnetic form of Mg improved morphological abnormalities and motor dysfunctions significantly, whereas other forms of Mg were ineffective.Diabetic neuropathy (DN) is the most common late complication of diabetes showing an increasing prevalence [1]. Sixty per cent of patients with diabetes show evidence of peripheral nerve disease [2].…”
mentioning
confidence: 66%
See 3 more Smart Citations